The Effectiveness of Using "Pictures Me Reading" for Teaching Vocabulary in a Thailand's Primary School - Leedangsa, Assareena; Lalee, Laila; Akem, Asma (English Language in Focus (ELIF), 2024)
The aim of study was to determine the effectiveness of as the technique used picture me reading in improving students' English vocabulary. This study applied quantitative method with experimental research design by using both Pre-test and Post-Test as the one class of 3th graders of Thammasat Wittaya School, Thailand consisting of 20 students become the sample of the research. The data were collected by using pre-test and post-test which measured students' role play before and after the research. These data were analyzed statistically by using paired- sample t-test. The findings revealed that the students performed better in the post- test than in the pre-test in which they reached mean score of 37 in the pre-test and increased into 75.7 in the post-test. Thus, this research concluded that Role play used as technique in improving vocabulary skills of 3th grade students was effective.